Model Konseptual Faktor Kadar Caj Perkhidmatan Bangunan Kediaman Berstrata - Kasim, Rozilah; Hizam, Nurin Izazi Hazuyah (Research in Management of Technology and Business, 2023)
The issue of non-uniformity of service charge rates has caused dissatisfaction among residents of strata residential buildings. This is because the determination of the charge rate imposed by the management body is still unclear and differs between residential stratified buildings. Furthermore, the guidelines for determining service charge rates for stratified residential buildings have not yet been standardized. Therefore, this paper aims to develop a conceptual model to identify the factors determining service charge rates for stratified residential buildings. A systematic and in-depth literature review was carried out using databases such as google scholar, research gate, science direct and Emerald. The data obtained was analysed using thematic analysis where each main theme was compiled to form the conceptual framework of the model. The results of the study can be used as a guide and reference for the management body in determining the service charge rate for stratified residential buildings. Keywords: Service Charges, Stratified Residential Building, Conceptual Model